Pemberdayaan Tertib Administrasi PKK Kelurahan Limus Nunggal - Antony, Antony (PT. Alahyan Publisher Sukabumi, 2023)
The empowerment of orderly PKK administration is one solution to the problems faced by PKK members, namely the lack of understanding related to PKK administrative order. The purpose of this activity is to increase the understanding and skills of PKK members of Limus Nunggal Village regarding PKK administration. The method of implementing this activity is empowerment for PKK members of Limus Nunggal Village. The partner in this empowerment activity is the Limus Nunggal Village Subdistrict. The evaluation was carried out by doing direct practice and bimtek before and after the delivery of the material, and the result was that the comprehension ability and skills of the participants increased by 36.25%.